Język, logika i soteriologia - Lipnicki, Michał (Investigationes Linguisticae, 2012)
The aim of the article is to describe the notion of language and some “logical’’ ideas that were developed by one of the greatest figure of Buddhist philosophy – Nāgārjuna. Moreover, this article will present the importance of the logical analysis of language as a factor contributory to the achievement of the ultimate goal of any Buddhist activity – enlightenment (nirvāṇa).